(untitled) (Práxis Educativa, 2022)
Based on broader research and having the historical and dialectical materialism as theoretical support, this text aims to reveal the relationship of forces between the United Nations Educational, Scientific and Cultural Organization (UNESCO) and the Brazilian Union of Secondary Students (UBES), In the materialization of Law no. 13.415/2017 – High School Reform. For that, documents produced by UNESCO, regulations, notes and other texts produced by UBES are analyzed, and semi-structured interviews carried out with six students who held positions of director of the entity in the period between 2018 and 2020. The analyzes are guided by the categories of hegemony and relationship of forces extracted from Antonio Gramsci’s thinking. In the end, it is concluded that the guidelines of UNESCO and the demands of the student movement are antagonistic, because, in one hand, there is the defense of capitalist interests, and, on the other hand, there is a concern with a broader formation focused on social praxis. In the materialization of the proposal for the new High School, there was loss to the student demands and the supremacy of bourgeois interests defended by the international agency. Keywords: Relationship of forces. Hegemony. UNESCO. Student movement. Law no. 13.415/2017.